Choco Blanco Cafe / Norina Alias...[et al.] - Alia, Norina; Kipli, Dk Nur Dayana Amani; Abdullah, Natasha Alysha; Daring, Jane Peloque; Muktar, Hasniah (Faculty of Business Management, 2013)
We have started our own business as partners, and all of us decided and agreed to call our business as Chaco Blanco Cafe. The idea of forming this business came from all of us. The main idea was we only want to focus and producing product based on white chocolate. But, all of us afraid that our business will not be able to compete with other existing product in the market. Then we decided to open a cafe that can produce a lot of food product based on our main ingredients that is white chocolate. This also will make our cafe different from the other existing cafe. Each of the partners is also acting as the head department with one person as the General Manager. We will run this business at Kk Times Square as it a new developed area and has gained the attention from the people from all across Kota Kinabalu, Sabah. We seized this opportunity because, it will surely add up the competition and choices for the people to make.